Expression of recombinant feline tumor necrosis factor is toxic to Escherichia coli. - Otto, C M (1995)
The tumor necrosis factor (TNF) genes from cats, horses, and pigs have all been cloned into the pFLAG-1 fusion protein expression vector (International Biotechnologies, Inc., Kodak, New Haven, Conn.). Growth curves for Escherichia coli containing the pFLAG-1 vector alone and the pFLAG-1 vector containing the TNF gene from each species were determined by visible light spectrophotometry (at 600 nm). Porcine TNF, equine TNF, and feline TNF cultures had slower doubling rates than cultures containing the pFLAG-1 vector alone. Cultures of cells transformed with feline TNF reached peak densities at 3 to 4 h and then decreased to near initial densities prior to the recovery of growth. The induction of expression with isopropyl-beta-D-thiogalactopyranoside (IPTG) arrested the growth of fresh feline TNF cultures for 6 h, which was followed by complete recovery. This inhibition occurred in two strains of E. coli (LL308 and JM101). Induced feline TNF cultures expressed the TNF-FLAG fusion protein for the first 6.5 h. Uninduced cultures expressed low levels of fusion protein. The feline TNF-pFLAG-1 vector was purified from cells expressing fusion protein and from cells with recovered growth curves. Sequencing the vector demonstrated the complete feline TNF gene and tac promoter in cells expressing the fusion protein and a deletional mutation of the tac promoter site in recovered cells. In contrast to equine and porcine TNF, the expression of recombinant feline TNF is toxic to E. coli. Alterations in protein folding and the prevention of secretion of the feline protein may explain the toxic effect.